Diversity, intensity and prevalence of parasites of cichlids in polluted and unpolluted sections of Eleyele Dam, Ibadan, Nigeria. (UNED Research Journal, 2017)
This study aimed to investigate the diversity, intensity and prevalence of parasites in Cichlids. A total of 354 specimens of cichlids was sampled in polluted and unpolluted ends of Eleyele River, Ibadan, Nigeria and examined for parasites. The total prevalence was 57.34%. Recovered parasites were Clinostomum tilapiae, Euclinostomum heterostomum, Neascus, Allocreadium ghanensis, Phagicola longa, Alloglossidium corti and the acanthocephalan; Acanthogyrus tilapiae and Acanthella. Clinostomum tilapiae had higher prevalence and abundance (42.90%) with Allocreadium corti recording least abundance (0.49%). Tilapia zilli was the most abundant (41.53%) among the fish hosts but Oreochromis niloticus harboured the highest percentage of parasites (80.00%). The fish hosts in the polluted end of the river harboured the highest percentage of parasites (71.18%) against (43.50%) parasites recovered from the unpolluted end. There was a significant difference in the parasites harboured. Heavy infection with a broad number of parasites in fish hosts could reduce performance and productivity of the species, especially in fish farming.
Keywords: Cichlids; Parasites; Polluted; Unpolluted; Eleyele Dam